Peran Komunikasi Bisnis dalam Membangun Kepercayaan dan Loyalitas Konsumen UMKM di Indonesia - Widia .; Nabila Nur Balqis; Risti Nur Fasana; Fitri Yani (CV. ITTC INDONESIA, 2026)
The objective of this scientific study is to examine the role of business communication in building consumer trust and loyalty among small- to medium-sized enterprises across Indonesia. This research employs a qualitative approach using a literature review method, specifically by analyzing various scientific journals and relevant sources published after 2020. The findings indicate that business communication delivered clearly, openly, and responsively plays a crucial role in enhancing consumer trust. Customers tend to feel more confident in making transactions when the information provided is easy to understand and supported by prompt responses from business operators. Additionally, the use of digital platforms such as social media and marketplaces can strengthen the relationship between business operators and customers. The level of trust that is built subsequently contributes to increased consumer loyalty, as demonstrated through repeat purchases and recommendations to others. Thus, business communication serves not only as a medium for conveying information but also as a strategic effort to foster long-term relationships with consumers.